2022
DOI: 10.1080/20964129.2021.2024454
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamic of environmental indices of watershed sustainability in connection with land-use change

Abstract: Exploring spatial and temporal land-use changes is valuable for local governments to address issues of sustainability and planning policy where urbanization and industrialization are taking place. Besides anthropogenic effects, natural driving forces like climate change may also affect sustainability. However, such relationships have not been studied minutely. Hence, this study first investigates the land-use changes and their relationship with land surface temperature (LST) for the Shazand Watershed, Iran, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…Accordingly, the P index was four low, relatively low, moderate, and relatively high, with a relative coverage of 39.74%, 30.16%, 25.9%, and 4% of the total watershed. Meanwhile, anthropogenic criteria (i.e., 65.6%), hydrologic criteria (i.e., 24.86%), and climatic criteria (i.e., 9.54%) have participated in determining the P index, which was consistent with the related studies of Ding et al (2008), Ebrahimi Gatgash and Sadeghi (2022), Hazbavi et al (2018), Mao et al (2014), Mirchooli et al (2022), andMosaffaie et al (2021) on the role of anthropogenic factors in determining the health of ecosystems. Government-related variables were also listed by Mao et al (2014) as the most crucial elements affecting the health of Lake Ulansuhai in China.…”
Section: Zonation Of the Health Index In The Galazchai Watershedsupporting
confidence: 86%
See 2 more Smart Citations
“…Accordingly, the P index was four low, relatively low, moderate, and relatively high, with a relative coverage of 39.74%, 30.16%, 25.9%, and 4% of the total watershed. Meanwhile, anthropogenic criteria (i.e., 65.6%), hydrologic criteria (i.e., 24.86%), and climatic criteria (i.e., 9.54%) have participated in determining the P index, which was consistent with the related studies of Ding et al (2008), Ebrahimi Gatgash and Sadeghi (2022), Hazbavi et al (2018), Mao et al (2014), Mirchooli et al (2022), andMosaffaie et al (2021) on the role of anthropogenic factors in determining the health of ecosystems. Government-related variables were also listed by Mao et al (2014) as the most crucial elements affecting the health of Lake Ulansuhai in China.…”
Section: Zonation Of the Health Index In The Galazchai Watershedsupporting
confidence: 86%
“…The maximum and the minimum value of bio‐density were for subwatershed 15 with a value of 3.38 and subwatersheds with no population. Ebrahimi Gatgash and Sadeghi (2022), Mirchooli et al (2022), Mosaffaei et al (2021), and Yasuri et al (2012) reported that increasing biodensity causes pressure on soil and water resources and, in addition to destruction and pollution, leads to migration and other socioeconomic consequences. The high concentration of population in the subwatersheds 13 and 15 caused more pressure to reach needs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, the increased value of NDVI indicated expansion in the agricultural areas. According to Mirchooli, 49 NDVI values greater than 0.3 indicates healthy vegetation and increased vegetation cover. MODIS time-series data (Figure 8) also confirm an increase in NDVI and EVI data from 2000 to 2020.…”
Section: Resultsmentioning
confidence: 99%
“…2 The study indicates that tree cover areas was converted into the built-up area (impervious development) in the Prayagraj landscape, which has significantly disturbed the urban terrestrial radiation balance and upsurged the land surface temperature contributing to climate change on micro to synoptic-scale. 49 Furthermore, spatial analysis shows that the conversion of tree cover and fallow land into built-up areas was most prevalent in the city's South, Southwest, North and Northwest part.…”
Section: Land Cover Changementioning
confidence: 99%